Learning Outcome Evaluation Techniques - Padila, Amanda Rezeki; Akbar, Arif; Andini, Dwi; Prastiwi, Dinda Aulia; Sembiring, Lisa Seprina Br (Lembaga Riset Mutiara Akbar, 2025)
For a teacher, to know student learning outcomes, they must have knowledge about evaluating learning outcomes, which has various stages, so that the evaluation carried out can be measured and accurate. This research was conducted to examine how learning outcomes evaluation techniques can be implemented. This research is qualitative in nature by analyzing several literature books and as the main data source. The results of the research are the steps for evaluating learning outcomes, namely, preparing a plan for evaluating learning outcomes, collecting data, verifying data, processing and analyzing data, providing interesting interpretations and conclusions, and nothing more about the evaluation results. By using learning outcomes evaluation techniques in the form of test techniques, objective techniques and non- test techniques.